Preliminary design of a mechanically pumped cooling system for active antennae - Gerner, H.J. van; Berg, T.H. van den; Es, J. van; Tailliez, A.; Walker, A.; Ortega, C.; Centeno, M.I.; Castro, C. (50th International Conference on Environmental Systems, 2021)
The satellite telecommunications industry is currently undergoing significant evolutions. Future communication satellites need to accommodate a rapidly growing demand in data transfer, combined with more flexibility. For example, there is a strong need for Very High Throughput Satellites capable of delivering up to Tb/s over wide coverage areas and an active phased array antenna is a powerful enabler to achieve that. However, cooling of active antennas requires the use of a highly efficient thermal control system because it has many heat sources (hundred or more), high local heat fluxes (20W/cm at evaporator interface), high overall dissipation (around 10 kW), and isothermal requirements on the amplifier chain. These conditions are very difficult to solve with current thermal control solutions (e.g. heat pipes or loop heat pipes), but require a two-phase mechanically pumped fluid loop (MPL). In a MPL, a pump circulates a fluid which evaporates when it absorbs the waste heat from the active antenna. In the EU funded IMPACTA project, a demonstrator for such a MPL is being designed and built. This paper describes the preliminary design for this demonstrator, including the fluid selection and tests on evaporator samples.